1971
DOI: 10.1177/002224297103500206
|View full text |Cite
|
Sign up to set email alerts
|

Premiums—Forgotten by Theory

Abstract: Marketing theory has not focused much attention on the use of premiums. This article attempts to define and identify elements of behavioral theory relevant to the problem of premium effects. An experimental premium offer was utilized with Stockholm housewives to produce the intriguing results presented in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The second gift design dimension, gift relatedness , refers to the link between a gift and the gift-giving firm, as well as its products and services, which can be related or unrelated (Keh and Lee 2006; Yi and Jeon 2003). We do not predict that either related or unrelated gifts are more effective per se, because both company related (e.g., free company products) and company unrelated (e.g., free products from other companies) gifts can increase perceptions of relationship investment (Seipel 1971). But providing either related or unrelated gifts should influence the associations that customers assign to the gift (Bodur and Grohmann 2005).…”
Section: Theoretical Modelmentioning
confidence: 86%
“…The second gift design dimension, gift relatedness , refers to the link between a gift and the gift-giving firm, as well as its products and services, which can be related or unrelated (Keh and Lee 2006; Yi and Jeon 2003). We do not predict that either related or unrelated gifts are more effective per se, because both company related (e.g., free company products) and company unrelated (e.g., free products from other companies) gifts can increase perceptions of relationship investment (Seipel 1971). But providing either related or unrelated gifts should influence the associations that customers assign to the gift (Bodur and Grohmann 2005).…”
Section: Theoretical Modelmentioning
confidence: 86%
“…Jones (1964) has developed a comparable theory of ingratiation in which gift-giving is one means of securing at least feigned affection. And Seipel (1971) has demonstrated that the use of advertising premiums may create in recipients a need to reciprocate by purchasing the advertiser's products.…”
Section: The Process Of Gift Exchangementioning
confidence: 99%
“…Chang argued, however, that premiums do not always add value to a product and that certain contextual factors may moderate their effectiveness. Following Seipel's (1971) finding that badly chosen premiums can lead to a negative perception of a brand, Simonson and Carmon (1994) even claimed that when consumers perceive premiums as adding little or no value, premiums can negatively affect brand choice (see also Chang, 2009). It appears from these findings that choosing (the "right") premium is key.…”
Section: University Of Antwerp Belgiummentioning
confidence: 99%